ANALISIS KEMAMPUAN PENALARAN MATEMATIK SISWA SMP PADA MATERI SEGITIGA DAN SEGI EMPAT - Andani, Fitri; Zulfikar, Ryan Nizar; Rukman, Nia Kurniaty (MEGA: Jurnal Pendidikan Matematika, 2024)
This research aims to determine the form of students' mathematical reasoning abilities in mathematics learning at Muhammadiyah Kupang Middle School. The research uses descriptive qualitative methods with subjects determined to be 6 children with high, medium and low abilities. on class VIII A level. The data collection techniques used in this research are tests, interviews and documentation. Test sheets and interview sheets. There are three stages of data analysis techniques, namely: Question instrument analysis, Data Clarification, Conclusion drawing, and data validity. Based on the analysis, it was found that there are forms of learning difficulties mathematical reasoning students in learning mathematics (1) Difficulty in calculating squares and rectangles, triangle and quadrilateral theorems, Solving problems related to triangles and quadrilaterals, and Solving problems related to triangles so that it is difficult to work on problems. (2) Difficulty in distinguishing unit numbers, tens, hundreds and thousands, but this difficulty does not match what is experienced by students because there are students who can still work on the questions given and there are still students who still find it difficult to differentiate, (3) Weak ability to identify and solve math story problems, so that students find it difficult to do story problems. There is a fact that the self-confidence of Muhammadiyah Kupang Middle School students is quite positive, but there are still some students who still show an anxious, shy and nervous attitude when asked to answer questions from the teacher